Evening Primrose Extracts Inhibit PDGF-BB-Induced Vascular Smooth Muscle Cell Proliferation and Migration by Regulating Cell-Cycle-Related Proteins - Lee, Jin-Ho; Kim, Min Jeong; Woo, Keun-Jung; Hong, Joonpyo; Kim, Sun-Hong; Kim, Tack-Joong (Current issues in molecular biology, 2022)
The proliferation and migration of vascular smooth muscle cells (VSMCs) are important factors in the occurrence of cardiovascular diseases, such as blood flow abnormalities, stroke and atherosclerosis. Evening primrose, known as Oenothera biennis, is a plant native to Korea that exerts physiological activities, such as antioxidant effects, the inhibition of lipid accumulation and the prevention of muscle atrophy. However, the function of evening primrose stem (EVP) in the regulation of VSMC proliferation and migration and the underlying mechanisms have not been identified. In this study, the effect of EVP on the platelet-derived growth factor (PDGF)-induced proliferation and migration of VSMCs was investigated. The results show that PDGF-BB-induced proliferation of VSMCs was inhibited by EVP at concentrations of 25, 50 or 100 μg/mL in a concentration-dependent manner, and a migration assay showed that EVP inhibited cell migration. Cell cycle analysis was performed to confirm the mechanism by which cell proliferation and migration was inhibited. The results indicate that proteins involved in the cell cycle, such as cyclin, CDK and phosphorylated Rb, were downregulated by EVP at concentrations of 100 μg/mL, thereby increasing the proportion of cells in the G0/G1 phase and inhibiting cell cycle progression. In the PDGF receptor (PDGFR) signaling pathway, phosphorylation of the PDGFR was inhibited by EVP at concentrations of 100 μg/mL, and PLCγ phosphorylation was also decreased. The PDGF-BB-induced effect of EVP on the proliferation of VSMCs involved the inhibition of Akt phosphorylation and the reduction in the phosphorylation of MAPK proteins such as ERK, P38 and JNK. In conclusion, the results demonstrate that EVP inhibited PDGF-BB-induced VSMC proliferation and migration by regulating cell-cycle-related proteins.